Translational Research on Trichoderma: From 'Omics to the Field - Lorito, Matteo; Woo, Sheridan L; Harman, Gary E; Monte, Enrique (Annual review of phytopathology, 2010)
Structural and functional genomics investigations are making an important impact on the current understanding and application of microbial agents used for plant disease control. Here, we review the case of Trichoderma spp., the most widely applied biocontrol fungi, which have been extensively studied using a variety of research approaches, including genomics, transcriptomics, proteomics, metabolomics, etc. Known for almost a century for their beneficial effects on plants and the soil, these fungi are the subject of investigations that represent a successful case of translational research, in which 'omics-generated novel understanding is directly translated in to new or improved crop treatments and management methods. We present an overview of the latest discoveries on the Trichoderma expressome and metabolome, of the complex and diverse biotic interactions established in nature by these microbes, and of their proven or potential importance to agriculture and industry.